Be Strong Enough to Say No: Self-Affirmation Increases Rejection to Unfair Offers - Gu, Ruolei; Yang, Jing; Shi, Yuanyuan; Luo, Yi; Luo, Yu L. L.; Cai, Huajian (Frontiers in Psychology, 2016)
We propose that self-affirmation may endow people more psychological resources to buffer against the negative influence of rejecting unfair offers in the classic ultimatum game (UG) and further lead to a stronger tendency to reject those offers. We test this possibility by conducting an event-related potential (ERP) study about the UG, with the ERP component P3 as an indirect indicator of psychological resources. Participants were randomly assigned to the affirmation or control condition and then completed the UG through electrophysiological recording. As expected, the behavioral data indicates that compared with unaffirmed ones, affirmed participants were more likely to reject unfair UG offers; the electrophysiological data indicates that compared to the unaffirmed, affirmed participants showed a greater P3 in response to the presentation of an offer. These findings suggest that psychological resources may play a role in rejecting others beyond the fairness concern, and additionally shed light on the neural mechanisms underlying self-affirmation.